The Guidelines For Democracy Promoting of Schools in Nakhon Sawan Municipality Nakhon Sawan Province: Nakhon Sawan Rajabhat University - Silabutr, Baoubon; Kreuasang, เครือแสง (MCU Haripunchai Review, 2025)
This study aimed to 1) study the problems in promoting democracy in schools of Nakhon Sawan Municipality, Nakhon Sawan Province, 2) study the process of promoting democracy in schools of Nakhon Sawan Municipality, Nakhon Sawan Province, and 3) study the approach to promoting democracy in schools of Nakhon Sawan Municipality, Nakhon Sawan Province. The groups used in the study were: This study was conducted by a qualitative research method, collecting data from documents and collecting field data through in-depth interviews with individuals or experts involved in promoting democracy for at least 3 years, by selecting 17 people. The instruments used in the study were interview forms, and qualitative data were analyzed by content analysis. The research results revealed that: 1) Problems in promoting democracy in schools of Nakhon Sawan Municipality include lack of support from the community, some teachers still lack understanding of democracy, limited budget, and an education system that focuses more on achievement than life skills. In addition, conservative culture is an obstacle to students’ open-mindedness. 2) The process of promoting democracy in schools must start with policies that support student participation, promote analytical thinking, and create cooperation with the community. Activities that help promote democracy include student council elections, debates, and student development projects. Integrating democratic principles into the curriculum and practical training are important approaches. There should be continuous monitoring and evaluation. 3)The approach to promoting democracy should focus on student participation, develop a curriculum that integrates knowledge, and promote the role of the community and teachers. If all sectors cooperate, it will help develop youths into quality citizens.